Should the sympathetic nervous system be a target to improve cardiometabolic risk in obesity? - Lambert, Elisabeth A.; Straznicky, Nora E.; Dixon, John B.; Lambert, Gavin W. (American journal of physiology. Heart and circulatory physiology, 2015)
The sympathetic nervous system (SNS) plays a key role in both cardiovascular and metabolic regulation; hence, disturbances in SNS regulation are likely to impact on both cardiovascular and metabolic health. With excess adiposity, in particular when visceral fat accumulation is present, sympathetic activation commonly occurs. Experimental investigations have shown that adipose tissue releases a large number of adipokines, cytokines, and bioactive mediators capable of stimulating the SNS. Activation of the SNS and its interaction with adipose tissue may lead to the development of hypertension and end-organ damage including vascular, cardiac, and renal impairment and in addition lead to metabolic abnormalities, especially insulin resistance. Lifestyle changes such as weight loss and exercise programs considerably improve the cardiovascular and metabolic profile of subjects with obesity and decrease their cardiovascular risk, but unfortunately weight loss is often difficult to achieve and sustain. Pharmacological and device-based approaches to directly or indirectly target the activation of the SNS may offer some benefit in reducing the cardiometabolic consequences of obesity. Preliminary evidence is encouraging, but more trials are needed to investigate whether sympathetic inhibition could be used in obesity to reverse or prevent cardiometabolic disease development. The purpose of this review article is to highlight the current knowledge of the role that SNS plays in obesity and its associated metabolic disorders and to review the potential benefits of sympathoinhibition on metabolic and cardiovascular functions.